The Application of Christian Ethical Principles in Social Life - Wilson Simanjuntak; Dinar Sianturi; Rajiman Simanullang; Rumondang Bellania Sibarani; Heryana Munte; Desi Kristina Manalu (Sean Institute, 2025)
Modern social life faces increasingly complex moral challenges. Polarization, declining empathy, intolerant behavior, crises of integrity, and the degradation of ethics in both public and digital interactions indicate a weakening of society’s moral foundations. These conditions call for an ethical approach capable of restoring the quality of social relationships and strengthening human values. This study aims to examine the application of Christian ethical principles—such as love, justice, integrity, forgiveness, and service—as a foundation for shaping constructive social behavior. The method employed is a systematic and narrative literature review, analyzing journals, academic books, and theological articles published between 2020 and 2025 that are relevant to Christian ethics and social life. The findings indicate that the value of love enhances social solidarity; justice strengthens the protection of vulnerable groups; integrity builds public trust; forgiveness supports social reconciliation; and service promotes humanitarian action and community empowerment. These findings demonstrate that Christian ethics can make a meaningful contribution to addressing contemporary moral issues, although challenges such as secularization, individualism, and pressures from digital culture remain. The implications of this study underscore the importance of internalizing Christian ethical values within families, churches, educational institutions, and communities in order to build a more humane, just, and dignified society.